Effects of ambient ozone (O3) concentrations on the growth performance of rice (oryza sativa var. Mr 219) treated with different nutrient regimes in the muda area, Malaysia - Ali, Sharifah Azlina (2007)
Ozone (O3) is a secondary gaseous pollutant produced through photochemical reaction known to have substantial impacts on agricultural production in North America and Western Europe. In Malaysia, emissions of O3 precursors such as non-methane hydrocarbons and nitrogen dioxide are rapidly increased due to urbanization, industrialization and the increasing number of motor vehicles. Furthermore climatic condition in the country is frequently favourable for the formation of high concentration of O3. It can threaten the rice production which is important to the country as it is the staple food for the vast majority of the population. In this study, different nutrient regimes were employed to assess the impact of ozone on the growth and yield of variety of local rice (Oryza sativa L.) at Muda area in three different ambient ozone (O3) concentrations. A controlled experiment involving ambient ozone (non-filtered air) and filtered air treatment in open top chambers demonstrated protective effects of nutrient against ozone. The study found that ozone significantly reduced the growth of rice plant by inhibiting photosynthetic rate, stomatal conductance, transpiration, tiller number and biomass. The result also demonstrated that the growth of rice plant was significantly increased when adding 25% of nutrient regime from normal practices. The relationship between grain dry weight, ozone dosage (AOT40) and the optimum nutrient regime expressed through a fitting linear model produced the following equation: Grain Yield Weight (N125) = (-0.00045*AOT40)+(124.3953).